Corrosion Rates Measurements By Linear Polarisation and AC Impedance Techniques Using Different Steel Bars and Acidic Solution - Turu’allo, Gidion (SMARTek, 2006)
The corrosion rate of steel bars in concrete was affected by concentration of acid or pH level of concrete environment which covered the steel bars. This research was conducted by using different acid and concentration with different diameter and kind of steel bars. The results obtained from the test using both the polarisation resistance (LPR) and the AC impedance techniques are similar. This is because the acidic environment supports the corrosion process. It is also found that the type and diameter of bars immersed in acid solution and the concentration of acid are the determining parameters of the corrosion rates of the bars. Even the length of test period also affects the corrosion rates as the polarisation resistance decreases by time.